2016
DOI: 10.1007/s11769-016-0819-9
|View full text |Cite
|
Sign up to set email alerts
|

High resolution land cover datasets integration and application based on Landsat and Globcover data from 1975 to 2010 in Siberia

Abstract: Land cover is recognized as one of the fundamental terrestrial datasets required in land system change and other ecosystem related researches across the globe. The regional differentiation and spatial-temporal variation of land cover has significant impact on regional natural environment and socio-economic sustainable development. Under this context, we reconstructed the history land cover data in Siberia to provide a comparable datasets to the land cover datasets in China and abroad. In this paper, the Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…A total of ten GEE clusters were identified, and these included papers related to tidal flats, Landsat time series, land surface temperature, wetlands, the recursive hierarchical segmentation method (RHSEG), central Asia, land-use change, nighttime lights, the NDVI, and yield estimation. The clustering results suggested that GE was widely applied as a virtual Earth in studies on ship detection [77][78][79][80][81][82][83], land-conversion mapping [84][85][86], glacial geomorphology [6,[87][88][89][90][91], and the Earth's lithosphere [92].…”
Section: Knowledge Base Analysismentioning
confidence: 99%
“…A total of ten GEE clusters were identified, and these included papers related to tidal flats, Landsat time series, land surface temperature, wetlands, the recursive hierarchical segmentation method (RHSEG), central Asia, land-use change, nighttime lights, the NDVI, and yield estimation. The clustering results suggested that GE was widely applied as a virtual Earth in studies on ship detection [77][78][79][80][81][82][83], land-conversion mapping [84][85][86], glacial geomorphology [6,[87][88][89][90][91], and the Earth's lithosphere [92].…”
Section: Knowledge Base Analysismentioning
confidence: 99%
“…We use the quality assessment (QA) flag to select the best quality pixels in each of the MODIS products. The land cover maps of Siberia in the 1970s and in 2010s are based on the previous work of our research group [38], which were extracted from the global land cover data and the Landsat TM and MSS data through interactive interpretation. All of the products used in the study were transformed to the Albers Equal Area projection at a resolution of 1 km.…”
Section: Study Area and Data Processingmentioning
confidence: 99%
“…To avoid the impact of land cover changes on the phenology variation, only the unchanged forest during 1992 to 2015 was analyzed in this paper. Due to fewer human activities, the land use and land cover changes were not significant from 1975 to 2010 in Siberia [33]. Although the land use changes were significant in Northeast China from the 1980s to 2000, the forests changes mainly concentrated on deforestation [34].…”
Section: Datamentioning
confidence: 99%